1995
DOI: 10.1111/j.1469-8137.1995.tb04297.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon allocation and water use in juvenile Douglas fir under elevated CO2

Abstract: SUMMARYIn this study the impact of an elevated CO, level on allocation of assimilates and water use efficiency of Douglas fir [Pseudotsiiga menziesii (Mirb.) Franco] was investigated. Juvenile Douglas firs were exposed to a long-term treatment at 350 and 700^1 T' CO^ for 14 months and subsequently crosswise transferred to phytotrons for a short-term treatment with 350 and 700 fi\ 1"^ COj for 4 wk in an atmosphere continuously labelled with "CO^. No interactive efTects on total net uptake of ^^COj between long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Elevated CO 2 may have stimulated early growth of the seedlings with the effect disappearing over time as observed previously in Douglas-fir by Gorissen et al (1995). In our study, root biomass was higher from soil cores taken in elevated compared with the ambient CO 2 chambers in fall Table 1.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Elevated CO 2 may have stimulated early growth of the seedlings with the effect disappearing over time as observed previously in Douglas-fir by Gorissen et al (1995). In our study, root biomass was higher from soil cores taken in elevated compared with the ambient CO 2 chambers in fall Table 1.…”
Section: Discussionsupporting
confidence: 56%
“…Franco) is the most important timber species in the Pacific Northwest of the United States and southern British Columbia, Canada (Little 1971), yet Douglas-fir has not been intensively studied in terms of responses to global climate change (Mote et al 1999;Franklin et al 1991). There have been a few studies on the short-term responses (~3-14 months) of Douglas-fir to elevated CO 2 in containers under controlled environments (Gorissen et al 1995;Mortensen 1994;Hollinger 1987). In general, these studies showed little effect of elevated CO 2 on growth or biomass accumulation or allocation for seedlings.…”
Section: Introductionmentioning
confidence: 97%
“…Hollinger (1987) found no difference in dry mass or relative mass allocation for P. menziesii with elevated compared to ambient CO 2 . Gorissen et al (1995) indicated that elevated CO 2 can have a short-term stimulatory effect on P. menziesii shoot growth, but that this effect may disappear over time. Brix (1967) reported more xerophytic P. menziesii leaves with higher temperatures (i.e., thicker, narrower, and heavier), but no effect of temperature on allocation of mass to stems and branches from roots.…”
Section: Douglas-fir and Climate Changementioning
confidence: 95%
“…However, the results observed from direct measurements of root respiration in response to elevated atmospheric CO # are varied (Rogers et al, 1994), with increases (Gorrisen, Kuikman & Van de Beek, 1995), decreases (Callway et al, 1994 ;Gifford, Lambers & Morison, 1985 ;Gonza ' lez-Meler et al, 1996) and no change (Stulen & Den Hertog, 1993) reported. Interestingly, Ryan et al (1996) have shown that for fine roots there is a strong relationship between root respiration and nitrogen content, suggesting that root activity varies with the protein content of the tissue.…”
Section: mentioning
confidence: 98%